Synthesis, Characterization, and Photochemical Properties of a New Square Mn(I)-Ru(II) Complex Using Pyrazine as Bridge Ligand - Inara de Aguiar; Simone D. Inglez; Antonio Claudio Tedesco; Rose Maria Carlos (Journal of Spectroscopy, 2013)
The photochemical properties of the complexes cis,fac- (I), cis-[Ru(phen)2(pz)2]2+ (II), and fac-Mn(CO)3(pz)2Br (III) where phen is phenanthroline and pz is pyrazine in acetonitrile solution are reported. The three complexes were characterized using 1H NMR, UV-vis and FTIR spectroscopy and electrochemical (cyclic voltammetry and spectroelectrochemical) techniques. The complexes show intense absorption in the visible region assigned to the population of MLCT excited states. The absorption spectrum of I is the sum of the spectra of the mononuclear species II and III, and the two oxidation potentials at +1.10 and +1.56 V versus Ag/AGCl observed in I are ascribed to the different coordination environments of metal centers. The photolysis in the acetonitrile solution resulted in the pz dissociation to give the monoacetonitrile complexes for I, II, and III, respectively.